TAHLILU MAWAD AD DIRASIYAH FI KITAB AL ARABIYAH AL MUFRIHAH - NI'matun Najah (Jurnal Al-Maqoyis, 2019)
Good material and appropriate books, as needed, will help the students and the teacher while teaching. The Arabic Language Development Unit Program is obligatory for all university students at the State Islamic University of Antasari in Banjarmasin. This program is one of the conditions for obtaining a bachelor's degree. This research aims to analyze the book "Al-Arabiya Al-Mufarriha 2" from the linguistic aspect,  teaching objectives, and the element of exercises. The type of this research is qualitative desk research with an analytical and descriptive approach. The researcher designed the design of this research as follows: The researcher began to take the data related to and needed to analyze the book “Al-Arabiya Al-Mufarriha 2”, the researcher determined the desired objectives for analyzing the data, and at the end, the researcher began to explore the crucial aspects of the book “Al-Arabiya Al-Mufarriha 2” of the advantages and disadvantages according to the objectives. The results of this research are the vocabulary and exercises from the book that are appropriate and consistent with the goals of teaching; some of the images used did not match the vocabulary intended for training.